THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) IN EDUCATION: CHALLENGES AND PROSPECTS (Ustozlar uchun, 2026)
In the contemporary era of global digitalization, integrating Information and Communication Technologies (ICT) into the educational framework is no longer an optional luxury but a core necessity. The shift from conventional pedagogical strategies to digital-centric models has fundamentally altered the interaction between teachers and students. This paper examines the diverse impacts of ICT on learning outcomes while identifying the primary barriers to its successful adoption.